1968
DOI: 10.1152/ajplegacy.1968.215.5.995
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate metabolism in contracting dog skeletal muscle in situ

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

1971
1971
1986
1986

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…During the 3 h studied in the present investigation the increase in glycogen synthesis after contraction was not large enough to restore glycogen to the level observed before contraction. Similar results have been reported for the in situ preparation of the gastrocnemius-plantaris muscle group of the dog, stimulated 5 time+ for 60 min (Chapler and Stainsby 1968). In that preparation complete recovery of the glycogen was not obtained within the 2 h studied.…”
Section: Discussionsupporting
confidence: 89%
“…During the 3 h studied in the present investigation the increase in glycogen synthesis after contraction was not large enough to restore glycogen to the level observed before contraction. Similar results have been reported for the in situ preparation of the gastrocnemius-plantaris muscle group of the dog, stimulated 5 time+ for 60 min (Chapler and Stainsby 1968). In that preparation complete recovery of the glycogen was not obtained within the 2 h studied.…”
Section: Discussionsupporting
confidence: 89%
“…The reasons why these studies in contrast to the present study did not convincingly reveal the significance of an intact sympathoadrenal system for the glycogen depletion during exercise are likely to be found in the use of less efficient sympathectomy procedures (Gollnick et al 1970, Maling et al 1966 (Gollnick et al 1970, Sembrowich et al 1974 or in the employed exercise procedures. It has been repeatedly observed that glycogen depletion can be elicited in isolated, perfused skeletal muscle by electrical stimulation (Berger et al 1975, Chapler and Stainsby 1968, Costin et al 1970, Helmreich and Cori 1966, Karlsson, Rosell and Saltin 1972. Furthermore, the capacity for work performance is reduced in patients with McArdle's disease, in whom muscular glycogenolysis is inhibited by a deficiency of glycogen phosphorylase (Pearson, Rimer and Mommaerts 1961).…”
Section: Discussionmentioning
confidence: 99%
“…These values are somewhat higher than those of Zierler et al [41], who estimated that the oxidation cf glucose by the forearm muscle of man accounts for about \Q% of the total oxygen consumption. Other groups have reported values ranging from 0 to 60 for the percentage of oxygen consumption accounted for by glucose oxidation in skeletal muscle [12]. The relative amounts of carbohydrate versus lipid utilized by adult cardiac muscle range widely and are influenced by the hormonal and physiologic condition of the animal [10,27,34,39]; the same is probably true of voluntary skeletal muscle but less data are available on this tissue [12].…”
Section: Discussionmentioning
confidence: 99%